Aplikasi Pemandu Wisata Berbasis Android Untuk 10 Wisata Bali Baru - Firdaus, Musnadil; Wiyono, Slamet; Af'idah, Dwi Intan; Hidayattullah, Muhammad Fikri (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
Tourism has a very significant role in the Indonesian economy. In 2016, the Indonesian government prioritized 10 tourism destinations as "10 New Bali Tourism". However, tourists often face difficulties in finding accurate and efficient information about public facilities at tourist attractions. To overcome this problem, this research aims to develop an Android-based tourist guide application. This application is designed to help tourists find facility information quickly and accurately. This research was carried out through a series of stages, including design, analysis, design, implementation, testing and application maintenance. The result of this research is the development of a tour guide application that is useful for tourists. This application makes it easy for them to find accurate information about public facilities around the tourist attractions they visit. Unit testing of this application shows that no errors were found in the application functions. Usability test results were also very positive, with 88% of tourist users stating they were willing to use this application again in the future. This shows that this tour guide application has succeeded in providing an effective solution to the problems faced by tourists in searching for information on facilities at tourist attractions. Thus, this application can be a valuable tool in enhancing the tourist experience and supporting the growth of the Indonesian tourism industry. This research has produced an Android tourist guide application to facilitate travelers in finding public facilities at the "10 New Bali Tourism" destinations. With an 88% user satisfaction rate, the main contribution involves improving the traveler experience, supporting the growth of the tourism industry, and making a positive contribution to the Indonesian economy.